The Precautionary Principle. Issue 3 (May 2015) - Simpson, Kathleen Rice
<x xml:space="preserve">Abstract</x> Two new resources support the concept of avoiding interventions during childbirth unless needed based on the condition of the mother and baby. Unnecessary interventions are not benign and may be associated with unintended harm.